The evolution of decision and experienced utilities - Arthur J. Robson; Larry Samuelson (Theoretical Economics, 2011)
Psychologists report that people make choices on the basis of "decision utilities'' that routinely overestimate the "experienced utility'' consequences of these choices. This paper argues that this dichotomy between decision and experienced utilities may be the solution to an evolutionary design problem. We examine a setting in which evolution designs agents with utility functions that must mediate intertemporal choices, and in which there is an incentive to condition current utilities on the agent's previous experience. Anticipating future utility adjustments can distort intertemporal incentives, a conflict that is attenuated by separating decision and experienced utilities.
Keywords: D11; D03; 330; Evolution; decision utility; experienced utility; focusing illusion